2015
DOI: 10.1007/s10549-015-3556-3
|View full text |Cite
|
Sign up to set email alerts
|

Who may benefit from preoperative breast MRI? A single-center analysis of 1102 consecutive patients with primary breast cancer

Abstract: Several authors question the potential benefit of preoperative magnetic resonance imaging (MRI) against the background of possible overdiagnosis, false-positive findings, and unnecessary resections in patients with newly diagnosed breast cancer. In order to reveal a better selection of patients who should undergo preoperative MRI after histological confirmed breast cancer, the present analysis was implemented. We aimed to evaluate the influence of preoperative breast MRI in patients with newly diagnosed breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 35 publications
2
30
0
2
Order By: Relevance
“…Contralateral BC has been shown to increase in those with ILC and breast MRI should be considered (14,15). Women with dense breasts also pose a challenge because the sensitivity of mammography is significantly decreased and focused breast ultrasound can miss extensive and multicentric disease (5,16). MRI is used in planning for partial breast irradiation because these patients will not receive sterilizing effect of whole breast irradiation (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contralateral BC has been shown to increase in those with ILC and breast MRI should be considered (14,15). Women with dense breasts also pose a challenge because the sensitivity of mammography is significantly decreased and focused breast ultrasound can miss extensive and multicentric disease (5,16). MRI is used in planning for partial breast irradiation because these patients will not receive sterilizing effect of whole breast irradiation (17).…”
Section: Discussionmentioning
confidence: 99%
“…These situations include evaluation of patients with invasive lobular carcinoma (ILC), which can be difficult because of a unique growth pattern and an increased risk of contralateral BC (14,15). Women with dense breasts have decreased mammography sensitivity which can also pose a challenge (5,16). MRI should also be used in planning for partial breast irradiation because these patients will not receive the sterilizing effect of whole breast irradiation (17).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…42 A single-centre analysis of 1102 consecutive patients with primary breast cancer found that pre-menopausal females with dense breasts and patients with lobular histology seemed to benefit from pre-operative MRI. 43 The controversy over pre-operative staging breast MRI is not likely to be resolved any time soon. Future research including prospective randomized multi-institutional trials involving large numbers of patients is needed to further define the role of preoperative breast MRI in light of the low recurrence rate of breast cancer with the current standard treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
“…For determining the extent of the lesion and the presence of multifocal or multicentric lesions, patients with breast carcinoma undergo preoperative evaluations including breast magnetic resonance imaging (MRI), which has proven to be the most sensitive tool for the detection of breast carcinoma (4)(5)(6)(7). Even though the use of preoperative breast MRI is increasing, controversy still exists for low specificity, unnecessary mastectomies, and cost-effectiveness (8).…”
Section: Introductionmentioning
confidence: 99%